Enhancing Self-Esteem in Patients with Low Self-Esteem Through SP1–SP4 Nursing Interventions - Nova Herliana; Wawan Rismawan (FORIKES, 2026)
Low self-esteem is a common negative symptom observed among patients with mental disorders and can significantly affect their self-confidence and social interaction abilities. This condition often leads patients to feel worthless, withdraw from their environment, and experience difficulties in performing daily activities. The purpose of this case report is to describe the application of nursing interventions using the Implementation Strategies (SP1–SP4) to enhance self-esteem in patients experiencing low self-esteem. The method employed is a case report based on the nursing care process, including assessment, diagnosis, intervention, implementation, and evaluation. The subjects of this report were four patients diagnosed with low self-esteem. The interventions provided included establishing a therapeutic relationship, identifying patients’ positive abilities, and training them in simple activities such as making their beds, washing dishes, and performing light exercise. The interventions were carried out over six days with daily monitoring of patient responses. The results demonstrated a gradual improvement in patients’ self-confidence, ability to maintain eye contact, social interaction, and independence in performing daily activities. In conclusion, the implementation of the SP1–SP4 strategies was effective in improving self-esteem and enhancing independence among patients with low self-esteem.Keywords: low self-esteem; nursing interventions; psychiatric nursing; self-confidence